1998
DOI: 10.1159/000019059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of Second and Fourth Components of Complement and Their Genes in Systemic Sclerosis and Association of HLA Alleles A1, B8 and DR3 with Limited and DR5 with Diffuse Systemic Sclerosis

Abstract: Deficiency of the complement component C4 at the functional, protein and gene level and deficiency of complement component C2 at the functional level were investigated and HLA analysis was performed on patients with limited and diffuse systemic sclerosis (SSc). One of the patients with limited SSc (n = 15) had subnormal C4, 1 subnormal C2 and 1 subnormal C4 and C2 activities; the latter patient had HLA alleles A11;B35;Dw1 associated with type II C2 deficiency and therefore most likely had a defect at the C2 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…The DRB1*0301 allele group and DQB1*02, which are in linkage disequilibrium, were significantly increased in the lcSSc subset compared to the dcSSc subset (OR = 9.0 and 6.6, respectively). The association with DRB1*03 has been previously reported in some Caucasian populations (17).…”
Section: Human Leukocyte Antigen‐drb1 ‐Dqbi and ‐Dpb1*1301 Phenotsupporting
confidence: 59%
“…The DRB1*0301 allele group and DQB1*02, which are in linkage disequilibrium, were significantly increased in the lcSSc subset compared to the dcSSc subset (OR = 9.0 and 6.6, respectively). The association with DRB1*03 has been previously reported in some Caucasian populations (17).…”
Section: Human Leukocyte Antigen‐drb1 ‐Dqbi and ‐Dpb1*1301 Phenotsupporting
confidence: 59%
“…The frequency of the HLA-DR3 serotype was higher in patients of systemic sclerosis [ 10 , 11 ] but lower in Crohn’s disease [ 12 ]. On the other hand, the presence of the HLA-DR7 serotype was correlated with decreased risk of systemic sclerosis [ 13 ], but was associated with higher risk of Crohn’s disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The null C4A allele occurs in about 35% of all SLE patients compared with 10% of the general population (14). Recently Venneker et al (15), observed isolated partial and functional deficiencies of C4 in many family members of a proband with frontoparietal scleroderma. These authors hypothesized that hypocomplementemia can be determined also by a gene not linked to the HLA region.…”
Section: Discussionmentioning
confidence: 99%